Kazakhstan’s Transit Potential Development through Transformation of Logistics Processes as a Part of Economic Growth - Sayabek Ziyadin; Dimash Yergobek; Aigerim Kazhmuratova; Aigerim Kuralova (Communications - Scientific letters of the University of Zilina, 2020)
The rapid development of transport, the widespread introduction of modern transport technologies, close cooperation with Russia, China and other neighboring countries, will allow Kazakhstan to become a serious player in the transportation market between Europe and Asia in the coming years. Such existing transport potential directly affects the economic growth of the country which will lead to high living standard. The global movement towards digitalization is transforming the logistics industry, as well. The "digit" changes the channels of movement of goods, delivery formats and management processes. Development of e - commerce and the increasing supply requirements - multichannel, responsiveness, transparency, accuracy - stimulate retailers and logistics operators to increase efficiency of processes and introduce new technologies. Therefore, the ways of prosperity of Kazakhstani economy, through digitalization of logistics processes is considered in this article.